Performance of different categories of pome fruit nursery trees during the first year in orchards - Eigenhuis, Willem Johannes Hermanus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1996.